Ethnomathematics : Eksploration of Traditional Crafts Tapis Lampung as Ilustration of Science, Technology, Engineering, and Mathematics (STEM) - Suherman Suherman (EduMa: Mathematics education learning and teaching, 2018)
This study aims to exploration of traditional crafts Tapis Lampung as ilustration STEM. This research is a qualitative research with an ethnographic approach. The results showed that (1) Science: as an illustration of the ability of scientific knowledge and biological acculturation processes found in animal motive that describe the elements of science, such as the Tapis Tuho motive which has dragon animal motives, aro wood, stars silver, and sasab titled. (2) Technology: as an illustration of new technologies emerging from globalization with the entry of Islam in Lampung, the implications for communication and traffic between the Indonesian archipelago so that the use of shipping transportation is needed, can be explored from the existence of a Tapis Single Ship which shows the diversity of forms and construction. (3) Technology: as an illustration of engineering technology that is developed through an design process by integrating other elements, it can be explored from the mountains motives, dragon ship motives, and hill motives that resemble bridges. (4) Mathematics: as a geometrical illustration of transformation, which can be expressed as a form of translation, rotation), reflection, and dilation.. Through the investigation of Tapis Lampung, it can be used as a source to disseminate and provide information about Indonesian local wisdom to the world.